Recent advances in opioid prescription for chronic non-cancer pain. Issue 1036 (1st July 2011) - Snidvongs, Saowarat; Mehta, Vivek
Abstract : Chronic pain is pain that persists past the normal time of healing, and is seen as a common problem with a significant socioeconomic impact. Pharmacological management for chronic non-cancer pain also involves the prescription of opioids, with the aim of an improved quality of life for the patient. New guidelines have been published to aid prescribing clinicians improve opioid safety and patient care, and include recommendations on when to refer patients to a pain specialist. In recent years there has been a rapid increase in opioid prescription in the UK and USA, prompting further concern regarding opioid abuse and side effects. Opioid use may also result in physical dependence and tolerance. Earlier recognition and diagnosis of unwanted effects of long term opioid use is needed, such as opioid induced suppression of the hypothalamic–pituitary–gonadal axis, and opioid induced immunosuppression. Patients may themselves discontinue opioids, however, due to minor side effects. Recent advances in opioid prescription include the increasing use of transdermal preparations and extended release, oral, once daily preparations. New formulations of existing drugs have been developed, as well as a new chemical entity. Abuse deterrent formulations and delivery systems may prevent the artificial acceleration of drug delivery and reduce the potential for opioid addiction. Overdose concerns and the potential for fatal overdose may necessitate mandatory training for all clinicians who prescribe opioids. Despite the widespread use of opioids in the management of chronic non-cancer pain, significant research gaps remain. An improvement in the evidence base for its prescription is required.